2018
DOI: 10.5860/crl.79.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Use of Print and Electronic Books: A Use Study and Discussion

Abstract: This article outlines a study assessing and comparing the rate of use of nonreference print and electronic book collections acquired during the same time period at one academic library. Rate of use was examined for both collections by discipline and method of acquisition. IntroductionThis article outlines a study assessing and comparing the rate of use of nonreference print and electronic book collections by discipline and method of acquisition acquired during the same time period at one academic library. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…They state that "there is no consensus on how to reliably measure ebook usage," a complaint with which Fry concurs. 13 The field lacks standardized ways to compare print and e-book usage or standard ways to interpret electronic usage. Although COUNTER provides an international standard of what elements should be included in a usage report, the standards still allow for widely differing ways of measuring the extent of use.…”
Section: Methods Used In Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…They state that "there is no consensus on how to reliably measure ebook usage," a complaint with which Fry concurs. 13 The field lacks standardized ways to compare print and e-book usage or standard ways to interpret electronic usage. Although COUNTER provides an international standard of what elements should be included in a usage report, the standards still allow for widely differing ways of measuring the extent of use.…”
Section: Methods Used In Previous Studiesmentioning
confidence: 99%
“…Fry examined all the books acquired within the same time period, regardless of publication date. 33 Knowlton considered all print books acquired during a certain time period and compared these to e-books from the library's largest e-book collections. He also excluded print books that do not circulate.…”
Section: Methods Used In Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the author collected data that showed that BGSU's recently acquired, nonreference print monographs, beginning with those acquired in 2008-2009, were used at a much higher rate than is commonly expected in academic libraries. 50 As table 8 shows, the rate of use of these titles has continued to grow. These data support the fact that the longer a group of titles is available, the more will be used, an idea that was first noted for print books by Burrell in his seminal 1985 paper, which established what is known as the "80/20 rule."…”
Section: Use Of Print Books At Bgsumentioning
confidence: 99%
“…This advice by Coyle fits well with that given a generation earlier by Jim Collins, which is that the move from good to great will come through appreciating our current strengths, rather than trashing everything and waiting to be rescued by an outsider messiah. 11 I went ahead and listed some of our strengths: hospitality, circulating print collections, 12 physical meeting space, support for ministers. These strengths are not simply things we do well, but also part of our library's culture.…”
Section: The Culture Codementioning
confidence: 99%